2005
DOI: 10.1111/j.1095-8339.2005.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource limitation and pollen source (self and outcross) affecting seed production in two louseworts, Pedicularis siphonantha and P. longiflora (Orobanchaceae)

Abstract: Two animal-pollinated hermaphrodite plants, Pedicularis siphonantha and P. longiflora , have been used to investigate factors limiting seed production in natural populations. To evaluate the potential seed abortion due to resources limitation, seed development has been observed and seed count conducted twice. Seed production per capsule has been compared when flowers have been removed and in a control group. Open pollination has been investigated and pollen supplementation undertaken to estimate the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 52 publications
3
40
0
1
Order By: Relevance
“…Only a few empirical studies have simultaneously assessed resource and pollen limitation (Vaughton 1991;Campbell and Halama 1993;Mattila and Kuitunen 2000;Suzuki 2000;Yang et al 2005;Brookes et al 2008). Many of these studies demonstrated complex interactive effects between resource and pollen limitation of seed and fruit production, several of which are consistent with our model predictions.…”
Section: Seed Developmentsupporting
confidence: 80%
“…Only a few empirical studies have simultaneously assessed resource and pollen limitation (Vaughton 1991;Campbell and Halama 1993;Mattila and Kuitunen 2000;Suzuki 2000;Yang et al 2005;Brookes et al 2008). Many of these studies demonstrated complex interactive effects between resource and pollen limitation of seed and fruit production, several of which are consistent with our model predictions.…”
Section: Seed Developmentsupporting
confidence: 80%
“…We collected these inflorescences 1 wk later and counted seed production in four flowers on each inflorescence that had experienced the treatments. Previous study has shown that ovary expansion is a reliable indicator of fertilization because of seed abortion caused by inbreeding depression in this species (Yang et al 2005). To examine the capacity for autonomous self-pollination and therefore the importance of insect visitors to pollination, we bagged one inflorescence of eight individuals.…”
Section: Pollination Treatmentsmentioning
confidence: 99%
“…Although the visitation rate was not very low compared with other endangered species (e.g. 1.2 times higher (per flower per day) in Cimicifuga nanchuanensis, Qi et al 1998), the geitonogamy will lead to self-fertilisation and may cause inbreeding depression in self-compatible species (Young et al 1996;Yang et al 2005). Pollination by self-pollen and geitonogamous pollen exclusively decreased the fruit set (Phase II) compared with artificial outcross pollination.…”
Section: Mating Systemmentioning
confidence: 95%